N-Methyl Groups in Bacterial Lipids III. Phospholipids of Hyphomicrobia - Goldfine, Howard (1968)
The phospholipids of Hyphomicrobium vulgare NQ-521 have been separated by preparative thin-layer chromatography and analyzed by paper chromotography of the water-soluble products of acid and mild alkaline hydrolysis. The principal phospholipids are phosphatidyl ethanolamine (23%), phosphatidyl N,N′-dimethylethanolamine (36%), lecithin (29%), and phosphatidyl glycerol (10%). Three other strains of Hyphomicrobium were found to have similar phospholipid compositions. Growing cells incorporated the methyl group of methionine into lipid-bound N,N′-dimethylethanolamine and choline. Experiments with sonic extracts of H. vulgare NQ-521 and (14)C (methyl) S-adenosylmethionine demonstrated the formation of phosphatidyl N-monomethylethanolamine in addition to the dimethylethanolamine and choline phosphatides.